Implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Curriculum in PETE Study Program - Ali Budiman (Journal of Physical and Outdoor Education, 2023)
The Merdeka Belajar Kampus Merdeka (MBKM) Curriculum is a government policy that aims to encourage students to be able to master a variety of sciences as an effort to improve the quality of human resources in the world of work with global competitiveness. Universities are required to make curriculum adaptations related to the implementation of this MBKM. Based on this, this study aims to reveal the implementation of the MBKM program, the obstacles, and the impact that students and tertiary institutions have felt since implementing the MBKM on PETE student's. This research is a qualitative descriptive study using the PETE study program of STKIP Pasundan as the study population. A total of 5 people consisting of 3 students, 1 lecturer, and 1 curriculum developer became the research samples. The research instrument used was in-depth interviews related to the implementation of the MBKM program to the respondents. The data obtained were then analyzed using the Miles analysis model. Overall, the results of the study stated that the implementation of the MBKM program was going well at the PETE study program of STKIP Pasundan, there were no significant obstacles in the implementation process, and the students who took part in the MBKM program had many positive impacts.